Determinants of risk factors on dermatophytes infections on patients’ knowledge, attitude and hygiene practice among patients attending dermatology department in a government hospital in Setif Province, Algeria - Belmiloud, Boualem; Kadir Shahar, Hayati; Abdul Rahman, Hejar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Dermatophyte infections are superficial infections that affect the skin and are caused by fungi, namely dermatophytes. Objectives: This study aimed to determine the prevalence of dermatophyte infections among patients who attended the Dermatology Department in Setif public hospital, Algeria and to determine the associated risk factors to these infections. Methods: A cross-sectional study with a sample size of 400 respondents was designed to collect the data using a validated pre-tested questionnaire from February to June 2019. The collected data was then analyzed using IBM SPSS version 25. Results: The response rate was 98.4% (315 respondents) with an overall mean age (SD) of 38.81 (16.37) years old. The prevalence of dermatophyte infections among respondents was 33.7%, 26% of them have single infections. On the other hand, multiple logistic regression analysis showed an increased odd of having dermatophyte infections by three times among patients from low-income families (OR=3.23, 95% CI=1.09- 4.78, p=0.03). Similarly, the presence of chronic diseases led to a twofold increase in the odds of having dermatophyte infection among patients (OR=2.27, 95% CI=1.01-10.49, p=0.045). It was also found that poor attitudes towards preventing dermatophyte infections increased the odds of having dermatophyte infection by near to three times (OR=2.58, 95% CI=1.14-4.74, p=0.002). Conclusion: The high prevalence of dermatophyte infections presents a significant concern in Setif Province, Algeria. In this context, further efforts are needed to review the practiced control measures to optimize the effectiveness of these measures, which may reduce dermatophyte infections, especially among patients with chronic diseases.